2012
DOI: 10.1021/ja210784u
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Elucidation of Ovatoxin-a, the Major Toxin Produced by Ostreopsis ovata

Abstract: Since 2005, the benthic dinoflagellate Ostreopsis cf. ovata has bloomed across the Mediterranean basin, provoking serious toxic outbreaks. LC/MS studies have identified a number of palytoxin-like compounds, termed ovatoxins, along with trace amounts of putative palytoxin as the causative agents of the O. cf. ovata -related human sufferings. So far, any risk assessment for ovatoxins as well as establishment of their allowance levels in seafood has been prevented by the lack of pure toxins. The present paper rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(137 citation statements)
references
References 9 publications
5
132
0
Order By: Relevance
“…A concurrent NMR study that fully elucidated the structure of ovatoxin-a [20] proved validity of the HR LC-MS n -based approach in confirming all the structural hypotheses made.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…A concurrent NMR study that fully elucidated the structure of ovatoxin-a [20] proved validity of the HR LC-MS n -based approach in confirming all the structural hypotheses made.…”
Section: Resultsmentioning
confidence: 58%
“…A concurrent NMR study we carried out on pure ovatoxin-a [20] confirmed the presence in the molecule of the hydroxyl group at C-42, the absence of the hydroxyl group at C-17, and most importantly allowed to exactly locate the missing hydroxyl groups at C-44 and C-64, thus demonstrating that ovatoxin-a is the 42-hydroxy-17,44,64-trideoxy derivative of palytoxin.…”
Section: Fragmentation Pattern Of Ovatoxin-amentioning
confidence: 72%
See 1 more Smart Citation
“…The PLTX-group of toxins includes complex polyhydroxylated compounds with a lipophilic and a hydrophilic area. Different molecules related with the PLYX structure ( Figure 1) have been described: palytoxin-b, homopalytoxin, bishomopalytoxin, neopalytoxin, deoxypalytoxin, 42-hydroxypalytoxin, ostreocin-d, ovatoxin-a, -b,-c,-d, -e and -f and mascarenotoxin-a, -b and -c. However only the chemical structures of PLTX, ostreocin-d, ovatoxin-a and 42-hydroxypalytoxin have been characterized [4][5][6][7][8][9][10][11]. PLTX is a large molecule, with a molecular weight of 2659-2680 daltons depending on the origin [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, there has been increasing consensus in the scientific community regarding microalgae as at least one producer of the toxins, even though the biosynthetic pathways are still unclear and represent a field of open and ongoing research. In addition to O. siamensis, putative PLTX and analogues have been isolated from O. mascarenensis [29] and O. ovata [30][31][32][33][34][35]. Extensive studies on Ostreopsis samples has led to the identification of several PLTX congeners (Figure 2), including ostreocin-D [26,27], mascarenotoxins [29][30][31][32][33][34] and several ovatoxins, denoted ovatoxin-a, -b, -c, -d, -e [30][31][32][33][34] and ovatoxin-f [35].…”
Section: Introductionmentioning
confidence: 99%